Chapter Oral Health Advocates: A Nationwide Model for Pediatrician Peer Education and Advocacy about Oral Health - Charlotte W. Lewis; Lauren Barone; Rocio B. Quinonez; Suzanne Boulter; Wendy E. Mouradian (Hindawi Limited, 2013)
Objective. (1) To describe an innovative program training US pediatricians to be Chapter Oral Health Advocates (COHAs). (2) To provide insight into COHAs' experiences disseminating oral health knowledge to fellow pediatricians. Patients and Methods. Interviews with 40 COHAs who responded to an email request, from a total of 64 (62% response). Transcripts were analyzed for common themes about COHA activities, facilitators, and barriers. Results. COHAs reported positive experiences at the AAP oral health training program. A subset of academic COHAs focused on legislative activity and another on resident education about oral health. Residents had an easier time adopting oral health activities while practicing pediatricians cited time constraints. COHAs provided insights into policy, barriers, and facilitators for incorporating oral health into practice. Conclusions. This report identifies factors influencing pediatricians' adoption of oral health care into practice. COHAs reported successes in training peers on integrating oral health into pediatric practice, identified opportunities and challenges to oral health implementation in primary care, and reported issues about the state of children's oral health in their communities. With ongoing support, the COHA program has a potential to improve access to preventive oral health services in the Medical Home and to increase referrals to a Dental Home.